The EU agri-food system in the recent crisis scenarios - Carla Zarbà; Gioacchino Pappalardo; Roberta Selvaggi; Biagio Pecorino (Economia Agro-Alimentare, 2023)
The European Union agri-food system has faced major challenges in the last years due to the Covid-19 pandemic and the Russian-Ukrainian war. In a scenario where millions of people all over the world suffer from hunger, the uncertainty of food availability and commodity price surge have made it difficult for them to find and afford food on a large scale even in countries, which apparently are not exposed to those risks. Within the European Union (EU), this has depended upon the vulnerabilities and dependencies inherent in the agri-food system. In order to react and cope with emergency scenarios, the European Institution has adopted some temporary measures. The present paper, verifies the level of the EU agri-food Self-Reliance system through the development of Self-sufficiency calculation and the Import Dependency Index as well as the EU comparative advantage through the Gerard-Lafay Index and the relative comparative advantage (Vollrath). On the basis of the achieved results, recommendable actions have been suggested in order to secure the food supply on one hand, and satisfy the EU demand even in case of future adverse events, on the other. In addition, further actions that need to be taken, recommended by the European institutions, have been described.